Pemerolehan Ungkapan-Ungkapan Bahasa Arab Bagi Santriwati Baru di Pondok Pesantren Putri - Thoibatun Nafisah; Jasmani Jasmani; Hamidah Hamidah (Taqdir, 2021)
In a female Islamic boarding school in South Kalimantan, Arabic and English are applied in daily communication, both in formal and informal settings. Seeing the efforts of both the Islamic boarding school and the students themselves in mastering Arabic including its expressions, this qualitative descriptive study was carried out with the aim of describing how the students' Arabic expressions were obtained and also the types of expressions, because each Islamic boarding school and even each individual and group had individual efforts to improve Arabic language skills. Data were collected through interviews, observation and documentation from 15 new santriwati and a number of other informants who were then checked for data validity through data triangulation and analyzed at the stages of data collection, data reduction, data presentation and conclusion drawing. The results showed that the acquisition of Arabic expressions is obtained through listening to Arabic conversations both in formal and informal environments as well as through learning, both learning that has been determined by the Islamic boarding school such as memorizing the expressions on the media card, studying individually or studying in groups. The types of Arabic expressions obtained in the Islamic boarding school for girls are through listening and learning in the form of teachings, appeals and prohibitions. The implication of this research is that foreign language speaking skills will be easily mastered with a spirit of learning, learning strategies and the use of learning media.